2007
DOI: 10.1002/nau.20547
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of bladder dysfunction in idiopathic normal pressure hydrocephalus

Abstract: While incontinence can result secondarily from gait disturbance or dementia, detrusor overactivity mostly underlies urinary urgency/frequency and incontinence in iNPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 34 publications
4
74
0
6
Order By: Relevance
“…There are fewer studies about urinary incontinence in iNPH, but frequent urination due to decreased bladder volume and detrusor hyperactivity has been reported [22] . Besides these 3 symptoms, decreased motivation, easy tiredness, agitation or mood instability have been observed in 88% of iNPH cases [23] .…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer studies about urinary incontinence in iNPH, but frequent urination due to decreased bladder volume and detrusor hyperactivity has been reported [22] . Besides these 3 symptoms, decreased motivation, easy tiredness, agitation or mood instability have been observed in 88% of iNPH cases [23] .…”
Section: Discussionmentioning
confidence: 99%
“…114) In addition, overactive bladder was reported to be significantly correlated with enhancement of parasympathetic nerve activity on power spectral analysis of 24-hour electrocardiography-recorded R-R interval variability, and the variation returned to the normal level after a lumbar puncture test and shunt surgery. 76)…”
Section: -C Characteristics Of Urinary Dysfunctionmentioning
confidence: 99%
“…A definition of probable iNPH before shunt surgery was proposed in the SINPHONI diagnostic guidelines, based on 517 papers on diagnosis and 587 papers on therapy found using MEDLINE [6][7][8]. The inclusion criteria were: (1) age above 60 years; (2) one or more of the clinical triad of symptoms (gait disturbance, dementia, and urinary incontinence); (3) the presence of hydrocephalus, defined as an Evans' ratio (the ratio between the maximal width of the frontal horns and the internal diameter of the skull at the same level) above 0.30 on CT or MRI, often accompanied by a narrow CSF space at high convexity and a wide CSF space at the Sylvian fissure [4,9,10]; (4) a CSF pressure below 20 cm of water on the lumbar tap; (possible iNPH is diagnosed when criteria 1-4 are fulfilled); (5) improvement in clinical manifestations by the lumbar tap test, which is defined as 'positive' when the patient's total score on the iNPH grading scales (Japanese NPH grading scale-revised, JNPHGS-R) [6][7][8] (Table 1) decreased by one or more points after the removal of 30 ml CSF; (probable iNPH is diagnosed when criteria 1-5 are fulfilled); and (6) patient's informed consent. The exclusion criteria were: (1) other neurological diseases or non-neurological diseases; (2) increased CSF cell counts or total protein; and (3) previous illnesses that might cause ventricular dilatation.…”
Section: Subjects and A Jnphgs-r Bladder Subscalementioning
confidence: 99%
“…iNPH is characterized by a clinical presentation of gait disturbance, memory deficit, and bladder disorder (originally described as urinary incontinence, [1,2] but urinary urgency/frequency (also called an overactive bladder, OAB) often precedes it [4]), combined with dilated cerebral ventricles and normal cerebrospinal fluid (CSF) pressure. It is recently reported that severe bladder disorder in iNPH is predicted by right…”
Section: Introductionmentioning
confidence: 99%